Analysis of the Use of Interactive Learning Media on Student Learning Motivation - Malita Nurul Asrifah; Banun Havifah Cahyo Khosiyono; Berliana Henucahyani3 (Jurnal Pendidikan Anak, 2025)
Limited technological infrastructure, suboptimal teacher skills, and the dominance of conventional learning methods continue to hamper the implementation of interactive educational resources in elementary schools. This study aims to analyze the effect of interactive media on student learning motivation. The method is a qualitative case study of two teachers in grades 4 and 5. Data were obtained through observation, interviews, and documentation, then analyzed using the Miles & Huberman model, which includes data reduction, data presentation, and conclusion. The results show that interactive media can increase student engagement, enthusiasm, and understanding of the material, while also facilitating teachers in delivering learning and creating a more enjoyable and collaborative classroom atmosphere. The implications of this study emphasize the importance of improving teachers' competence and the availability of technological facilities so that the use of interactive media can operate optimally to enhance the quality of learning in elementary schools.